Short communication. Genetic diversity within Scorpiurus species from the Iberian Peninsula estimated using ITS DNA sequences - Visnevschi-Necrasov, T.; Harris, D. J.; Faria, M. A.; Pereira, G.; Nunes, E. (Spanish Journal of Agricultural Research, 2011)
Scorpiurus muricatus and Scorpiurus vermiculatus have been proposed as possible subjects for breeding programs to improve their potential as forage crops. However, prior to this genetic diversity between these species and within distinct populations should be assessed. We estimated diversity between populations from the Iberian Peninsula using ITS 1 and ITS 2 nuclear DNA sequences. Twelve haplotypes from 25 individuals were determined, and a network of relationships produced. Our results indicate considerable haplotypic diversity, but no deep subdivisions either within S. muricatus or between the two species. This means that no potential barriers to the proposed breeding programs were identified.